PEMBELAJARAN MENULIS DAN EVALUASI DI SEKOLAH SMPN 7 TARAKAN - Nursawaliza, Siti; Riyanti, Asih; Awaluddin, Ahmad Rahul; Syahirah, Arni; Wahid, Raka Zulkarnain (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
This research examines the implementation and effectiveness of writing learning activities as well as the evaluation system at junior high school 7 Tarakan. By using descriptive-qualitative approach, this study analyzes the methods of teaching writing skills, learning strategies applied by teachers, and evaluation techniques used to measure students' writing ability. Data were obtained through classroom observations, interviews with Indonesian language teachers, and analysis of learning documents. The results showed that collaborative and project-based approaches and writing learning were able to improve students' motivation and writing quality. Meanwhile, the evaluation system that combines formative and summative assessment provides a comprehensive picture of the development of students' writing skills. This study identifies some challenges such as time constraints and the heterogeneity of students' abilities, and provides recommendations for improvement in the form of developing more specific assessment rubrics and utilizing peer feedback to improve the writing learning process at  junior high school 7 Tarakan. ABSTRAKPenelitian ini mengkaji pelaksanaan dan efektifivitas kegiatan pembelajaran menulis serta sistem evaluasinya di SMPN 7 Tarakan. Dengan menggunakan pendekatan deskritptif-kualitatif, penelitian ini menganalisis metode pengajaran keterampilan menulis, strategi pembelajaran yang di terapkan oleh guru, dan teknik evaluasi yang digunakan untuk mengukur kemampuan menulis siswa. Data diperoleh melalui observasi kelas, wawancara dengan guru Bahasa Indonesia, dan analisis dokumen pembelajaran. Hasil penelitian menunjukan bahwa pendekatan kolaboratif dan berbasis proyek dan pembelajaran menulis mampu meningkatkan motivasi dan kualitas tulisan siswa. Sementara itu, sistem evaluasi yang menggabungkan penilaian formatif dan sumantif memberikan gambaran komperhensif terhadap perkembangan kemampuan menulis siswa. Penelitian ini mengedintifikasikan beberapa tantangan seperti keterbatasan waktu dan hotergenitas kemampuan siswa, serta memberikan rekomendasi perbaikan berupa pengembangan rubrik penilaian yang lebih spesifik dan pemanfaatan umpan balik sejawat untuk meningkatkan proses pembelajaran  menulis di SMPN 7 Tarakan.